The practice and rhetoric of prediction – the case in agent-based modelling. Issue 2 (4th March 2023) - Edmonds, Bruce
ABSTRACT: This paper looks at the tension between the desire to claim predictive ability for Agent-Based Models (ABMs) and its extreme difficulty for social and ecological systems, suggesting that this is the main cause for the continuance of a rhetoric of prediction that is at odds with what is achievable. Following others, it recommends that it is better to avoid giving the impression of predictive ability until this has been iteratively and independently verified, due to the danger of suggesting more than is empirically warranted, especially in non-modellers. It notes that there is a restricted and technical context where prediction is useful, that of meta-modelling – when we are trying to explain and understand our own simulation models. If one is going to claim prediction, then a lot more care needs to be taken, implying minimal standards in practice and transparent honesty about the empirical track record – the over-enthusiastic claiming of prediction in casual ways needs to cease.